The gospel of Judas a novel - Mawer, Simon 1948- (Little, Brown, 2001)
Father Leo Newman, a priest from Rome, struggles with the discovery of a fifth gospel, told from the point of view of Judas Iscariot, at the same time as he fights his impossible attraction to a married woman.
Keywords: Bible. -- N.T. -- Gospels -- Authorship -- Fiction; Klerus; British -- Italy -- Fiction; Catholics -- Fiction; Clergy -- Fiction; Italien; Italy -- Fiction; Christian fiction